The Differences in Thermal Breakdown of H2PtC16 and cisPt( NH3)2C12 in Carbon Furnace Atomic Absorption. - Haron, Md Jelas; Wan Yunus, Wan Md Zin (1989)
A study using a combination of thermogravimetric and x-ray diffraction analyses has shown that a solution of hexachloroplatinic acid (Hj'tCI(), usually used as a standard in atomic absorption spectrophotometric (AAS) measurements, was broken down to yield volatile PtCt before being converted to metallic platinum. On the other hand, a solution of cis-diaminodichloroplatinum(II) (cis-Pt(NH)zClz ; cis-DDP) was converted to metallic platinum in a single step. The differences in their thermal decomposition mechanisms could be one of the leasons as to why carbon furnace atomic absorption spectrophotometric (CFAAS) signal from Hj'tCI~ was found to be lower than that of cis-DDP in aqueous solution. INTRODUCTION Studies by earlier workers have shown differences in absorbance signals of platinum from different platinum complexes when analyses by flame AAS technique. For example, the platinum absorbance of ( H4)2PtC14 (50 ppm) is about twofold greater than that of ~PtCI6 (Macquet and Theophanides 1974) and the cis-DDP signal is about 12% higher than that of H2PtCI6 (Macquet et al. 1974). These differences are said to be due to the differences in thermal stability of the complexes. The ability of the more stable complex to survive as volatile species in the flame is greater than the less stable complexes; a volatile species is more easily decomposed to free atoms hence a higher AAS signal is obtained. (Macquet and Theophanides 1975